Results of investigating the characteristics of bone marrow in patients with squamous cell carcinoma of the head and neck, their clinical value - E. G. Timonina; N. N. Tupitsyn; S. O. Podvyaznikov; V. A. Spiridonova; M. A. Frenkel’; O. P. Kolbatskaya; O. A. Chegrinets (Опухоли головы и шеи)
To reveal the specific features of hematopoiesis in patients with head and neck squamous cell carcinoma (HNSCC), the authors analyzed the indicators of 41 bone marrow aspirates in relation to the clinical and morphological characteristics of the tumor and micrometastases detected in bone marrow. Puncture samples were morphologically and molecularly examined at the Laboratory of Hematopoiesis Immunology, N.N. Blokhin Russian Cancer Research Center. The found changes in the bone marrow cell composition in HNSCC patients showed themselves as an increase in the relative count of segmented neutrophils and a decrease in the level of immature granulocytes with no alternations in the neutrophil maturation index and in the percentage of granulocyte lineage cells. Bone marrow hypocellularity is a characteristic feature of high-grade HNSCC. The significantly enhanced leuko-erythroblastic ratio was due to a reduction in red blood cells: the erythroid cell maturation index rose, by increasing the percentage of bone marrow oxyphilic normoblasts in patients with locally advanced HNSCC. A highly sensitive method for detecting mRNA of the specific squamous cell carcinoma protein E48 was perfected using reverse-transcription polymerase chain reaction and Southern blotting, followed by an enzyme immunoassay that could recognize bone marrow micrometastases in 35 % of the patients with HNSCC. The patients with found bone marrow micrometastases showed a significant decrease in the proportion of polychromatophilic normoblasts and a significant increase in granulocytes in the presence of normal values of lymphocytes and other cellular elements of myelograms. It was established that in the presence of regional lymph node involvement, bone marrow micrometastases were significantly more frequently in the patients with HNSCC and tumor progression over a period of up to 9 months.